Challenges in Providing Holistic Nursing Care for Patients with Aplastic Anemia Using the Callista Roy Adaptation Model - Mahmud, Lia Rizqa Amelia; Nursanti, Irna (FORIKES, 2026)
Aplastic anemia is a hematological disorder that has complex physiological and psychosocial impacts on patients, thus requiring a holistic nursing care approach. The Callista Roy Adaptation Model conceptualizes individuals as adaptive systems who respond to various stimuli through coping mechanisms in order to achieve equilibrium. This scientific study aimed to describe the application of the Roy Adaptation Model in nursing care for a patient with aplastic anemia accompanied by gastrointestinal bleeding. The study employed a case report design using the nursing process approach, including assessment, diagnosis, planning, implementation, and evaluation based on Roy’s four adaptive modes: physiological–physical, self-concept, role function, and interdependence. The results of nursing care indicated that the management of focal stimuli in the form of bleeding, as well as contextual and residual stimuli influencing the patient’s psychological condition, facilitated more positive adaptive responses. Nursing interventions in the physiological–physical mode contributed to the stabilization of the patient’s condition, while supportive approaches, therapeutic communication, and education in the self-concept mode helped reduce anxiety and improve self-acceptance. Support for role function and interdependence through family involvement strengthened the patient’s adaptation process during treatment. In conclusion, the Roy Adaptation Model is effective as a conceptual framework for nursing care in patients with aplastic anemia, as it integrates physiological, psychological, and social aspects comprehensively.Keywords: aplastic anemia; Roy adaptation model; holistic nursing care; case report; anxiety